PROGRAM PENINGKATAN KETERAMPILAN PEMUDA DALAM MENGHADAPI PASAR KERJA DI KOTA PEKANBARU (Studi Kasus di Dinas Pemuda dan Olahraga Kota Pekanbaru) - Khairani Nst, Evi; Sari, Lapeti; Indrawati, Toti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is done at Pekanbaru's City on month of May 2015. To the effect of observational it is subject to be know juvenile forming program was impacted positive or negative to young men at Pekanbaru's City and to know resulting young men skill by on duty young men and Pekanbaru's City sport in face job market. This research utilize secondary data and primary data. Juvenile observational one goes along in executed program by on duty young men and olahrga is Pekanbaru's City year 2013 total one 150 person. Sample is taken by use of method Stratified Random Sampling which is sample take method by agglomerates population according to program as much 30 person, meanwhile analisis's method data that is utilized in this research is descriptive method. Base observational result to be known that young men already follow training has more skill, automatically have positive impact to young men at Pekanbaru's City, and labour exploit (young men) one that terampil or has skill more than resulting another young men by on duty young men and sport (At spore) Pekanbaru's city stills less optimal deep face job market, Working young men corresponds to its skill as much 18 person (60%) and one works in conflict with skill it as much 12 person (40%), if is seen from term skill type waits, kesesuain and accepted pay and less optimal human resource exploit (young men) terampil, more reverential reducing accords it skill type, the duration term waits to get work, inappropriate it talks shop with skill and insufficiently accords expected pay it with their one accepts.Keywords: Young men, skil, and Job market